The influence of Product Layout, Service, and Product Prices on Purchasing Interest in Traditional Market Retail Stores in Medan - Rifaldi Dwi Syahputra; Marliyah, Marliyah; Ahmad Syakir (Yayasan Payungi Smart Madani, 2025)
Competition between traditional markets and modern retailers is increasing, especially because traditional markets are sometimes considered less than optimal in terms of product layout, service quality, and price. However, some consumers still shop at traditional markets. This study aims to analyze how product layout, service, and price influence shopping interest in traditional market retail stores in Medan City. The selected population was customers shopping at retail stores in the Padang Bulan traditional market area of Medan, with a purposive sample of 80 participants. Data were processed using multiple linear regression analysis. The results obtained are that the product layout variable has a significant and positive effect on purchasing interest (p-value = 0.009). The service variable has a significant and positive effect on purchasing interest (p-value = 0.006). The product price variable has a significant and positive effect on purchasing interest (p-value = 0.000). It is recommended that further research expand the variables that influence purchasing interest, for example by including other variables such as advertising and product quality. To make the findings of this study more applicable and generalizable, further research can also be conducted in different locations with different market characteristics. Future research should include additional variables such as advertising, product quality, and digital engagement to gain a more comprehensive view of consumer behavior. Studies in other regions with different socio-economic or cultural backgrounds are also recommended to broaden the findings' applicability. This study provides valuable insights into traditional market competitiveness, showing that improving product layout, service quality, and pricing can enhance purchasing interest and help traditional markets remain relevant amid modern retail competition.